Research work in geography teaching: analysis of the work of grammar school students in Samobor in the school year 2019/2020 and 2020/2021 - Ivan Ivić; Karlo Mak; Ružica Vuk (Geoadria, 2021)
With the adoption of the new curriculum for the subject of Geography for primary and grammar schools in the Republic of Croatia (OG 7/2019), the teaching content was modernized and different approaches to learning and teaching geography were provided. The application of research methods and the preparation of research papers should be emphasized. Although the teaching of geography in the school years 2019/2020 and 2020/2021 in year 3 and 4 was still carried out according to the old curriculum from 1993, the students of Antun Gustav Matoš Grammar School in Samobor achieved the outcomes of GEO SŠ B.3.1./B.4.1. from the new curriculum, whose implementation is expected in this educational cycle. Within the stated outcomes, a student conducts geographical research related to the educational content and presents the results of the research work. In order to continuously monitor the progress of students, but also the quality of geography teaching, the work of grammar school students produced during their attendance in year 3 and 4 was analysed. For this purpose, a research paper assessment matrix was designed. A total of 56 papers were subjected to analysis, of which also from the school year 2019/2020 (year 3) and school year 2020/2021 (year 4). Qualitative analysis of the content of student papers was conducted using the MAXQDA software package. Specific examples of outcomes that were achieved or not were singled out. The most common problems to be highlighted when considering the content of the outcomes are the correct citation and quoting of literature and sources, then the processing of the data and their presentation, and finally the methods of data collection. Indeed, in most cases, already published graphical and cartographic appendices were downloaded, and data collection usually involved searching the Internet and using the first search results.